INFLUENCE OF RAINFALL ON THE DEFORMATION AND STABILITY OF A SLOPE IN OVERCONSOLIDATED CLAYS: A CASE STUDY - Alonso E.E.; Gens A.; Delahaye C.H. (My University, 2003)
The behaviour of an instrumented unstable slope in a profile of weathered overconsolidated clay has been analysed. Available field investigation data and laboratory tests were integrated in a coupled hydromechanical model of the slope. Particular attention was given to the unsaturated soil conditions above the water table and to the influence of the rainfall record. Recorded pore-water pressures helped to identify the hydrogeological conditions of the slope. The coupled model was used to compute slope deformations and the variation of safety with time. Actual rainfall records were also integrated into the analysis. Comparison of measurements and calculations illustrate the nature of the slope instability and the complex relationships between mechanical and hydraulic factors.
Keywords: OVERCONSOLIDATED CLAYS; SLOPE INSTABILITY; EXPANSION; FLOW; UNSATURATED SOIL; SUCTION; SAFETY FACTOR